Investigating User Acceptance Of Fintech Paylater With Technology Acceptance Model (TAM) - Herlina Herlina; Destriana Widyaningrum (Universitas Asahan, 2023)
The development of technology in the financial sector known as financial technology (fintech). The fintechs that is currently popular in the community is Fintech paylater. Fintech paylater is a type of financing that allows consumers to make online purchases by making installments or paying in the future. Fintech is widely applied in e-commerce and other selling platforms. The specific purpose of this study investigates the acceptance of fintect paylater users using the Technology Acceptance Model (TAM) model. The research method uses quantitative research, data analysis techniques using structural equation models (SEM) with path analysis (AMOS). The sample in this study were 101 respondents. The results showed that Perceived Ease of Use has a positive influence on Perceived Usefulness with a significant 1% and a relationship strength of 0.928, Perceived Usefulness has a positive influence on Attitude Toward Using with a significant 1% and a relationship strength of 0.551, Perceived Ease of Use has a positive influence on Attitude Toward Using with a significant 1% and a relationship strength of 0.416, Behavioral Intention to Use with a significant 1% and a relationship strength of 0.551, 416, Behavioral Intention to Use has a positive influence on Actual Use with a significant 1% and a relationship strength of 0.753, Attitude Toward Using has a positive influence on Behavioral Intention to Use with a significant 5% and a relationship strength of 0.451, Perceived Usefulness has a positive influence on Behavioral Intention to Use with a significant 5% and a relationship strength of 0, 433.